Ответ(ы) на вопрос:
[latex]1)\; \; \frac{a^2+b^2}{a^{\frac{4}{3}}-(ab)^{\frac{2}{3}}+b^{\frac{4}{3}}} = \frac{(a^2+b^2)(a^{\frac{2}{3}}+b^{\frac{2}{3}})}{(a^{\frac{2}{3}}+b^{\frac{2}{3}})\, ((a^{\frac{2}{3}})^2-a^{\frac{2}{3}}b^{\frac{2}{3}} +(b^{\frac{2}{3}})^2)} =\\\\=\frac{(a^2+b^2)(a^{\frac{2}{3}}+b^{\frac{2}{3}} )}{(a^{\frac{2}{3}})^3+(b^{\frac{2}{3}})^3} = \frac{(a^2+b^2)(a^{\frac{2}{3}}+b^{\frac{2}{3}})}{a^2+b^2} =a^{\frac{2}{3}}+b^{\frac{2}{3}} [/latex]
[latex]2)\; \; \frac{a^2-b^2}{-(a^{\frac{4}{3}}+a^{\frac{2}{3}}b^{\frac{2}{3}}+b^{\frac{4}{3}})} =- \frac{(a^2-b^2)(a^{\frac{2}{3}}-b^{\frac{2}{3}})}{(a^{\frac{2}{3}}-b^{\frac{2}{3}})(a^{\frac{4}{3}}+a^{\frac{2}{3}}b^{\frac{2}{3}}+b^{\frac{4}{3}})}=\\\\= -\frac{(a^2-b^2)(a^{\frac{2}{3}}-b^{\frac{2}{3}})}{a^2-b^2} =-a^{\frac{2}{3}}-b^{\frac{2}{3}}[/latex]
Не нашли ответ?
Похожие вопросы